Evaluación de la variabilidad del grosor de la pared duodenal del equino durante el ayuno y post ingesta líquida mediante técnicas ultrasonográficas (Veterinary Science, 2017)
The extractions of active principles present in plants are made with different solvent, and the solid remainders are used soon in the pharmacology investigations. In the specific case of Salpichroa origanifolia obtained a hidroalcoholic extract of high performance, which made difficult to the resuspention of it for the use in bioassays causing difficulties in the metering and problems in the absorption of the active principles. In this communication, we present the procedure to purify the hidroalcoholic extract of Salpichroa origanifolia using different methods like extraction and separation to obtain soluble solid fractions, in the same ones will investigate the active compound presence that allows determinate activity and the solubility in excipient to administer them to animals.
Keywords: Ultrasonography; Duodenal wall